UNITED NATIONS DEVELOPMENT PROGRAMME FOR ADDRESSING ENVIRONMENTAL PROBLEMS - Azamova Sitora Ayonovna; Arolova Zarina Lochin qizi (American Journals Publishing, 2025)
This article provides a comprehensive overview of one of the global issues – environmental problems – and discusses the United Nations Development Programme aimed at addressing these issues. It also highlights how this system helps coordinate efforts to protect nature.
Keywords: UN, strategy, environmental fund, ecology committee, environmental information, global.